The Historian and ‘the End of History’: Scientific Reflections of Milorad Ekmečić on the Problems of Historical Methodology in the Era of the Consumer Society - Aleksić, Jovan J. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This study is a part of a doctoral research project entitled Life and Work of Milorad Ekmečić (1928–2015), during which we realized that this distinguished Yugoslavian and Serbian historian in the late stage of his scientific career had shown particular interest in the problems of modern methodology of history. Studying his methodological work, which was very significant in the sense of quality if not volume, we came to the conclusion that he managed to achieve considerable results in that field, applying particular multidisciplinary and interdisciplinary approach. With his intellectual calmness, but also with experiential concern, he observed the world around him and the new problems faced by historiography at the turn of the century. He detected them on several levels: matter of periodization of contemporary history; philosophy and the sense of history after finalization of the Cold War conflict; the consumer society as a syntagm for contemporary history; the lack of auxiliary historical sciences which would study reports of contemporary media; the alteration of the nature of historical sources; the need to strengthen the outer and inner criticism; and the censorship and auto-censorship phenomena. In this context, he tried to offer authentical answers to numerous challenges of contemporary methodology and open new horizons for further research of this demanding scientific matter.